Investigation of Effects of Theoretical and Applied Education on Success and Recall Level in Analytical Chemistry - Mülazımoğlu, Ayşen Demir (Asian Journal of Education and Training, 2017)
In this study, a true-false test, selected from Analytical Chemistry textbook, was applied to investigate the effects of lesson learned in theoretical and applied in Analytical Chemistry to students’ achievement and recall levels. A 30-item test, selected from the basic subjects, was applied to a group of 81 students as the Secondary Chemistry Education Program of Faculty of Education. This group was selected from the 2nd, 3rd, 4th and 5th grades and tried to apply to the groups of approximate twenty students to compare female and male students in every class. As a result of the study, it has been determined that analytical chemistry topics are easier to understand and remember when they are thought as applied in the laboratory. Another result of this study was found that female students were more successful than male students. When the overall female students are taken into account along with the other lessons this is an expected result. One of the expected results of this study is that 2nd grade students were more successful than the other grades due to Analytical Chemistry and its application are given at the 2nd grade in the program. Besides all these results 4th graders are found to be more successful than 5th graders due to teaching of the pedagogical lessons at the last three terms of the program.